UPAYA PEMERINTAH INDONESIA DALAM MERESPON PENETAPAN TRAVEL WARNING DARI SINGAPURA TAHUN 2018 (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This study aims to find out how Indonesia's response after the travel warning was issued by Singapore using a qualitative descriptive method. The establishment of a travel warning policy by Singapore to Indonesia followed several issues that occurred in Indonesia, such as security issues and natural disasters. So that Indonesia makes efforts to take advantage of the political relations it has with Singapore by carrying out bilateral cooperation and diplomacy. By using the theory of tourism in International Relations and the concept of multi-track diplomacy is used to analyze the efforts of the Government of Indonesia. In an effort by the Government of Indonesia to focus on increasing the country's capacity building by using a tourism marketing strategy framework in it, namely: DOT (Destination, Origin, Time) and BAS (Branding - Advertising - Selling), as well as POSE (Paid Media, Owned Media, Social Media and endorser) with the assistance of various parties so as to produce cooperation in it. The resulting collaborations are: cooperation between the Government of Indonesia and the Government of Singapore, cooperation between the Government of Indonesia and non-government, cooperation between the Government of Indonesia and multinational companies, cooperation between the Government of Indonesia and the community and cooperation between the Government of Indonesia and the media. Keywords: Multi-Track Diplomacy, Tourism in International Relations, Indonesian Tourism, Travel warning.